A population-based observational study on the factors associated with the completion of palliative chemotherapy among patients with oesophagogastric cancer. Issue 3 (4th March 2015) - Groene, Oliver; Crosby, Tom; Hardwick, Richard Henry; Riley, Stuart; Greenaway, Kimberley; Cromwell, David
Abstract : Objectives: Palliative chemotherapy is routinely given to patients diagnosed with locally advanced or metastatic oesophagogastric (O-G) cancer. We examine which patients with O-G cancer in England receive palliative chemotherapy, and identify factors associated with treatment completion. Design: A prospective population-based observational study. Setting: All English National Health Service (NHS) trusts diagnosing patients with O-G cancer. Participants: Data were prospectively collected on patients diagnosed with invasive epithelial cancer of the oesophagus or stomach between 1 October 2007 and 30 June 2009 in English NHS hospitals, and those who had palliative treatment intent. Outcome measure: We calculated the proportion of patients with different characteristics (eg, age, sex, stage at diagnosis, performance status) starting palliative chemotherapy. Multiple logistic regression was used to identify characteristics associated with non-completion of chemotherapy. Results: There were 9768 patients in the study whose treatment intent was palliative. Among these, 2313 (24%) received palliative chemotherapy. It was received by 51% of patients aged under 55 years but only 9% of patients aged 75 years or over. Overall, 917 patients (53%) completed their treatment among the 1741 patients for whom information on treatment completion was recorded. Treatment completion ranged from 50–60% for patients with good performance status but was under 35% for patients aged 55 years or older with poor performance status. Treatment completion was not associated with site of cancer, pretreatment stage, sex, comorbidities or histology. Conclusions: Completion rates of palliative chemotherapy in patients with O-G cancer are low and elderly patients with poor performance status are very unlikely to complete a palliative chemotherapy treatment. Clinicians and patients should consider this information when balancing potential (survival) benefits, toxicity of treatment and its effect on quality of life.